PENGARUH INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI SEKTOR INDUSTRI DI PROVINSI PAPUA TAHUN 2007 – 2018 - Surani Surani; Mesak Iek; Halomoan Hutajulu; Yundy Hafizrianda (Journal of Management Small and Medium Enterprises (SMEs), 2021)
Labor absorption is still a major problem in a country, especially in Papua Province. Manpower is the most important factor in supporting economic development which aims to accelerate economic growth in a region. The industrial sector is one sector that has an important role in development. With the industrial sector, it will encourage other sectors such as the service sector and the agricultural sector. So that to encourage the industrial sector to create new jobs, it is necessary to invest both government and private investment. Investment itself has a function as a driving force for the economy, especially in terms of increasing employment. The purpose of this study is to examine and analyze the effect of investment on labor absorption in Papua Province. The development of investment and employment in Papua Province tends to fluctuate. This research was conducted over a period of 12 years from 2007 to 2018. By using secondary data obtained from the Central Bureau of Statistics and regional numbers (DDA). This study uses double log linear regression analysis method. The results of the study show that investment can significantly influence employment in the industrial sector in Papua Province. Thus, investment is one of the factor that can significantly influence labor absorption. The level of investment will affect the size of the absorption of existing labor Keywords: Investment, Labor Absorption, Industry